Предмет: Математика,
автор: icyberbaby
Решите уравнение
(3x-1)(2x-2)=(x-4)^3+7
svetazuna:
там точно 3 степень?
Ответы
Автор ответа:
1
Ответ:
6x^2-6x-2x+2=(x-4)(x-4)(x-4)+7
6x^2-6x-2x+2=x^3-4x^2-4x^2+16x-4x^2+16x+16x-64+7
-x^3+18x^2-56x=-59
-x^3+18x^2-56x+59=0
Пошаговое объяснение:
Автор ответа:
1
(3x-1)(2x-2) = (x-4)³+7,
6x²-6x-2x+2 = х³-12х²+48х-64 + 7,
6x²-6x-2x+2 - х³+12х²-48х+64 - 7 = 0,
-х³ + 18х² - 56х + 59 = 0
Похожие вопросы
Предмет: Математика,
автор: tocknadezda8
Предмет: Другие предметы,
автор: lyusenmahneva
Предмет: Литература,
автор: tarelka78
Предмет: Литература,
автор: volkoffvya4asl